Substancje ropopochodne w pyle drogowym w Zielonej Górze = Petroleum substances in the street deposits in Zielona Góra - Walczak, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of analyses of the petroleum substances content in road deposits, collected in the town of Zielona Góra. The content of total hydrocarbons in road deposits was compared with the standard specifying the maximum level of hydrocarbons in the soils of urban areas, in accordance with the Decree of the Minister of Environment from 9 September 2002. Street deposits have been determined as the material filling the streets.
Keywords: węglowodory; pyły drogowe; substancje ropopochodne; hydrocarbons; petrochemical substances; street dust